2008
DOI: 10.1086/529435
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Candidemia Caused by Non‐albicans CandidaSpecies VersusCandida albicansin the Intensive Care Unit

Abstract: Receipt of fluconazole and central venous catheter exposure were associated with an increased risk of BSI due to non-albicans Candida species, and total parenteral nutrition was associated with a decreased risk of BSI due to non-albicans Candida species, compared with BSI due to C. albicans. Patients without characteristics of infection due to non-albicans Candida species might benefit from empirical antifungal therapy with fluconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
150
5
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(180 citation statements)
references
References 42 publications
16
150
5
9
Order By: Relevance
“…33 It was observed that central venous cat heter exposure was associated with increased risk of BSI due to non-albicans Candida species and total parenteral nutrition was associated with a decreased risk of BSIs due to non-albicans Candida species compared with Candida species. However, in supplementary study it was concluded that there are multiple common risk factors for both albicans and non-albicans Candida BSIs and it is not possible to differentiate between these two groups based on clinical characteristics alone.…”
Section: Discussionmentioning
confidence: 99%
“…33 It was observed that central venous cat heter exposure was associated with increased risk of BSI due to non-albicans Candida species and total parenteral nutrition was associated with a decreased risk of BSIs due to non-albicans Candida species compared with Candida species. However, in supplementary study it was concluded that there are multiple common risk factors for both albicans and non-albicans Candida BSIs and it is not possible to differentiate between these two groups based on clinical characteristics alone.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract infection (UTI) is one of the most common types of nosocomial infections (Schaberg et al, 1991;Tamura et al, 2003) and more than 80 % of nosocomial UTIs are related to the use of medical devices such as urinary catheters (Febré et al, 1999;Harris et al, 1999;Douglas, 2002;Chow et al, 2008). Furthermore, Candida species are responsible for around 80 % of fungal infections in the hospital environment and 10-15 % ofinfections (Kojic & Darouiche, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…OR IC95% P A-OR IC95% P Se encontró que el principal agente causal de candidemia fue Candida albicans predominando sobre las especies no albicans; resultado que concuerda con los reportados por otros estudios realizados en nuestro país (15,20,21), y los descritos en otras investigaciones similares (22-24) realizadas en otros países, no obstante, difi eren a los reportados por Horn et al (3), quienes en una cohorte de 2009 pacientes con candidemia reportaron a las especies no albicans como agente causal en el 54,4% de los pacientes, pese a la presencia predominante de estas especies que pudo ser causada por la presión selectiva ejercida sobre Candida albicans por el uso previo de fl uconazol, el cual fue descrito por Chow et al (25) como factor de riesgo para candidemia por especies no albicans.…”
Section: Variableunclassified